ESTUDO DE CASO: ANÁLISES SAZONAIS DOS DADOS METEOROLÓGICOS E DE SO2 DE UMA REDE DE MONITORAMENTO DE QUALIDADE DO AR, COMO FERRAMENTA DE APOIO A GESTÃO DAS EMISSÕES DE SO2 DE UMA REFINARIA DE GRANDE PORTE - Rodrigues, William Senna (2008)
The present study structure is based on atmospheric emission sources inventory, geographical conditions evaluation and micrometeorology area information, over a predefined actuation area, which allows project sizing dimension and implementation over an air quality s network monitoring system. According to meteorological seasonal data analysis, that are put together and confronted with air quality data, referred to SO2, both obtained by the network monitoring system mentioned above. With that, we could confirm many theories on practice experiments, which can further generate a lot of conclusions and be used as a reference by other studies or researches, as well as be used as a support tool on SO2 emission s management of a large scale refinery.